2018
DOI: 10.3390/ijms19010192
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences and Molecular Bases of Low Fibrinogen Levels

Abstract: Abstract:The study of inherited fibrinogen disorders, characterized by extensive allelic heterogeneity, allows the association of defined mutations with specific defects providing significant insight into the location of functionally important sites in fibrinogen and fibrin. Since the identification of the first causative mutation for congenital afibrinogenemia, studies have elucidated the underlying molecular pathophysiology of numerous causative mutations leading to fibrinogen deficiency, developed cell-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 92 publications
(97 reference statements)
2
49
0
1
Order By: Relevance
“…
Hereditary fibrinogen disorders (HFD) are rare coagulation disorders resulting from mono-or bi-allelic mutations in fibrinogen genes. 1 According to the levels of fibrinogen activity and antigen, HFD are classified into quantitative (afibrinogenemia and hypofibrinogenemia) or qualitative (dysfibrinogenemia and hypodysfibrinogenemia) disorders. 2 The spectrum of symptoms is broad and heterogeneous among patients with HFD, even if bleeding is the most common complication of all HFD sub-types.
…”
mentioning
confidence: 99%
“…
Hereditary fibrinogen disorders (HFD) are rare coagulation disorders resulting from mono-or bi-allelic mutations in fibrinogen genes. 1 According to the levels of fibrinogen activity and antigen, HFD are classified into quantitative (afibrinogenemia and hypofibrinogenemia) or qualitative (dysfibrinogenemia and hypodysfibrinogenemia) disorders. 2 The spectrum of symptoms is broad and heterogeneous among patients with HFD, even if bleeding is the most common complication of all HFD sub-types.
…”
mentioning
confidence: 99%
“…In general, the bleeding phenotype in hypofibrinogenemic patients depends on the fibrinogen plasma value. Above 1 g/L, most patients are completely asymptomatic [38].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…3 Paradoxically, thrombosis in both venous and arterial sites are also a typical complication of congenital FIB disorders, in addition to bleeding symptoms. 4,5 In their study, the authors identified 2 novel FIB mutations in 2 Slovak families with quantitative FIB disorders and concluded the development of thrombotic complications was spontaneous since the patient and his son did not receive substitution therapy with the FIB concentrate in the period of their recurrent thromboses manifestation. 5 Due to their specific physiological characteristics, female patients tend to have congenital hypofibrinogenemia/afibrinogenemia, such as spontaneous recurrent abortion, menorrhagia, infertility, antepartum and postpartum hemorrhage, and so on.…”
Section: Introductionmentioning
confidence: 99%